Indigenous Healing of War-Affected Children in Africa - Green, Edward C.; Honwana, Alcinda (World Bank, Washington, DC, 2012)
The note identifies how an informal partnership between indigenous healers - with their ritualistic therapies - and donor-assisted programs - with emphasis on the family, and social adjustment - can provide a model of how indigenous, and Western scientific approaches can be pursued to provide war-torn children a maximum benefit. Symptoms of post-traumatic stress disorder (PTSD) have been exhibited in children during, and following war conflicts, and, while various organizations have developed types of psycho-social programs to assist war-affected children - namely through Western therapeutic techniques originally developed to treat American veterans of the Vietnam war - these remain at a very preliminary stage of development. The focus moreover, ignores local beliefs, and all its forms of ancestral spiritual forces intended to heal the affliction, and undermines as well, communal involvement in the healing process. Through two case studies - Angola and Mozambique - the note shows the tremendous knowledge of communities, in how to heal the "social wounds" in war-afflicted children, and adults. Evidence of this healing process is based on understanding mind afflictions, shared by spiritual interventions. What was though manifested, was the need in helping to find missing family members, in establishing schools, in creating job opportunities, to promote stable social environments. Thus organizations, and nongovernmental organizations should focus in local understanding, working to promote cultural environments, where children gain a sense of security.